SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN KELAYAKAN REKONSTRUKSI RUMAH MISKIN (Studi Kasus: Kabupaten Klaten) - Parjono, Parjono; Winarno, Wing Wahyu; Luthfi, Emha Taufiq (Jurnal Teknologi Informasi RESPATI, 2015)
ABSTRACTThis decision support system is a web-based system, which can help decision makers to use data from a variety of models to problems tersetruktur. In this thesis, has constructed a decision support system poorhouse reconstruction using AHP method (Analytical Heirarchy Process) which aims to help provide alternative solutions / proposals in decision-making, in this case that would be the Head of Social Service Klaten. Decision support systems are built based on 14 criteria poor from BPS (Central Bureau of Statistics) and giving preference value weighted interest where the total value of the weight should not be more or less than 100 (100%).Keywords: SPK, Reconstruction, AHP.